2016
DOI: 10.1007/s00193-016-0631-6
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation in rocket nozzles under high altitude condition

Abstract: The knowledge of flow separation in rocket nozzles is crucial for rocket engine design and optimum performance. Typically, flow separation is studied under sealevel conditions. However, this disregards the change of the ambient density during ascent of a launcher. The ambient flow properties are an important factor concerning the design of altitude-adaptive rocket nozzles like the dual bell nozzle. For this reason an experimental study was carried out to study the influence of the ambient density on flow separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The criteria used in figure 4 were also derived for higher Mach number and/or turbulent incoming boundary layer. Since the Mach numbers of the present study remain relatively moderate, the use a laminar separation criterion might also lead to more precise prediction [39]. Nevertheless, it is worth precising that these criterion are also obtained using data coming from different flow fields, and various experiments with different boundary conditions.…”
Section: Mean Flow Fieldmentioning
confidence: 99%
“…The criteria used in figure 4 were also derived for higher Mach number and/or turbulent incoming boundary layer. Since the Mach numbers of the present study remain relatively moderate, the use a laminar separation criterion might also lead to more precise prediction [39]. Nevertheless, it is worth precising that these criterion are also obtained using data coming from different flow fields, and various experiments with different boundary conditions.…”
Section: Mean Flow Fieldmentioning
confidence: 99%
“…Extreme caution should be taken during DBN wind tunnel testing, as many studies demonstrated that DBNs behaved differently depending on whether the tests were performed in altitude chambers or at ambient conditions. Varying the feeding total pressure during experiments also greatly influences the behaviour of DBNs as it changes the Reynolds number and modifies the effective wall shape of the sensitive inflection region [11,15,[19][20][21]. Though many of the previous studies provided significant information on DBN behaviour during the ascent and descent phases, only a few of them have focused on the control of transition and retransition, as well as side-loads generation in DBNs.…”
Section: Fig 2: Geometrical Parameters Of the Dbn Profile Used During...mentioning
confidence: 99%
“…n order to experimentally evaluate the highaltitude performance of the said nozzles, a high altitude test (HAT) facility system consisting of a supersonic exhaust diffuser is generally employed [1,2,3,4]. The main purpose is to reduce the nozzle back pressure sufficiently to have full flow at the design pressure [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a second-throat supersonic exhaust diffuser (STED) is numerically investigated using CFD [6]. Accurately predicting the starting pressure helps in constructing the test facility equipment appropriately and economically [2,3]. In the present study, the flow field in the STED is computed for cold flow of nitrogen gas (Ȗ=1.4) for simulating the highaltitude test configuration of a small-scale conical nozzle.…”
Section: Introductionmentioning
confidence: 99%